DEVELOPMENT OF PICTURE BOOK SERIES LEARNING MEDIA IN STRENGTHENING THE PANCASILA STUDENT PROFILE AT MTS MUHAMMADIYAH SANDEN - Ranita Eka Desti Rahmawati; Supri Hartanto Hartanto; Suyato Suyato; Ariani Songli; Maria Antoneta Karbeka (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to develop a *Picture Book Series* learning medium in order to strengthen the Pancasila student profile and analyse its application at MTs Muhammadiyah Sanden. This study uses a development research method with the ADDIE model, which consists of five stages, namely analysis, design, development, implementation, and evaluation. Data were collected through student response questionnaires in small and large scale trials, as well as observation, interviews, and documentation. The results of media validation by media experts and subject matter experts indicate that this media is highly suitable for use. In the implementation stage, the media was tested on two groups, namely a small-scale trial (5 students) and a large-scale trial (28 students), with results of 88% and 86.4%, respectively, in the very practical category. An evaluation was conducted to assess the success of the media, and revisions were made based on input from validators and the results of the trials. The results of the study show that the Picture Book Series media is effective as a learning tool for strengthening the Pancasila learner profile, with the use of stories and language appropriate to the level of understanding of junior high school students. The application of this media has succeeded in increasing student motivation and enthusiasm for learning